Organic Stereochemistry. Part 41. Issue 4 (10th April 2013) - Testa, Bernard; Vistoli, Giulio; Pedretti, Alessandro
Abstract This Part 4 continues a general presentation of the principles of stereochemistry with special reference to medicinal compounds and their interactions with biological systems. Here, we discuss and illustrate two major aspects of conformational isomerism, namely a) the concept of torsional isomerism about single bonds, and b) the intertwined conformational and configurational aspects of the stereochemistry of cyclic systems. The review begins with a brief reminder of the history and thermodynamics of conformational isomerism, and goes on to explain and illustrate the conventions and graphical representations used for conformers. Examples are then examined, beginning with ethane, the simplest one, and building up to more complex cases, documenting the attractive or repulsive role of substituents. A similar approach is applied when dealing with cyclic systems, although here the presentation necessarily takes into account configurational aspects specific to cyclic systems. The pharmacological implications of the concepts discussed here will be presented in Part 6.